The Interplay between the Duty not to cause Significant Harm and Equitable and Reasonable Utilization Principle - Mengesha, Zewdu Bashahider (Bahir Dar University Journal of Law, 2022)
This note tries to look in to the duty not to cause significant harm and its interplay with the equitable and reasonable utilizations rule. The presentation will explore lingering issues of preeminence between these two principles which may be crucial in understanding the full scope of riparian rights and obligations in the international water basin.